Positive electrode material precursor with stable structure as well as preparation method and application of positive electrode material precursor

The concentration of ammonium ions and carboxyl groups is adjusted through a specific complexing agent solution, and the crystal surface size of the precursor of high-nickel positive electrode material is controlled, which solves the problem of structural instability of high-nickel positive electrode material, and achieves the stability of positive electrode material performance and battery life. extend.

CN119390143APending Publication Date: 2025-02-07JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411522764.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

During the use of high-nickel positive electrode materials, cationic mixed discharge, intra-crystal cracks, inter-crystal cracks, structural degradation and interface side reactions, resulting in rapid decline in battery performance. The existing doping and coating methods cannot essentially solve structural loss. Stability problem.

Method used

By using a specific complexing agent solution, the ammonium ion concentration and carboxyl concentration are adjusted, the crystal surface size of the precursor of the positive electrode material is controlled, and its crystal structure is optimized, thereby improving the crystal structure stability of the positive electrode material.

Benefits of technology

The structural stability of the positive electrode material precursor is achieved, the service life of battery performance is extended, and the seed production is not required, and a positive electrode material precursor that meets the requirements of specific density, surface area and crystal surface size can be prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390143A_ABST
    Figure CN119390143A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material precursor with a stable structure and a preparation method and application thereof.The preparation method comprises the following steps that a metal salt solution, ammonia water, a complexing agent solution and a precipitator solution are mixed in a base solution in a parallel flow mode, a co-precipitation reaction is conducted, and the positive electrode material precursor with the stable structure is obtained; a complexing agent in the complexing agent solution comprises ammonia water and organic acid, and the molar ratio of ammonium radicals in the ammonia water to carboxyl groups in the organic acid is (0.1-5): 1. According to the preparation method of the positive electrode material precursor provided by the invention, by using the specific complexing agent solution, the crystal face size of the obtained positive electrode material is adjusted, and the crystal structure of the obtained positive electrode material precursor is optimized, so that the crystal structure stability of the corresponding positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and relates to a positive electrode material precursor and a preparation method and application thereof, and in particular to a positive electrode material precursor with a stable structure and a preparation method and application thereof. Background Art

[0002] As the nickel content increases, high-nickel cathode materials will experience problems such as cation mixing, intracrystalline cracks, intercrystalline cracks, structural degradation, and interface side reactions during use, which will lead to a rapid decline in battery performance. Doping and coating can improve these defects of high-nickel cathode materials to a certain extent, but cannot fundamentally solve the problem of structural instability of high-nickel cathode materials during use.

[0003] The performance of the positive electrode material is inherited from the corresponding positive electrode material precursor. By adjusting the grain size of the specific crystal plane of the high-nickel ternary positive electrode material precursor, the crystal structure of the high-nickel ternary positive electrode material precursor can be optimized, thereby improving the crystal structure stability of the positive electrode material.

[0004] CN116873985A discloses a method for preparing a nickel-based ternary cathode material precursor with a large (010) crystal surface area, wherein a nickel-based inorganic salt or a nickel-based organic salt is used as a raw material, and an ammonium-free complexing agent is used for reaction to prepare a flaky hydroxide seed with large primary particles and loosely distributed spherical shape that is conducive to growing into a large (010) crystal surface area precursor; a coprecipitation reaction is carried out with the hydroxide seed as a base material, and a nickel-based inorganic salt or a nickel-based organic salt is used as a raw material, and an ammonium-containing complexing agent is used for reaction to prepare a nickel-based ternary cathode material precursor with a large primary particle (010) crystal surface area and a spherical secondary particle. However, the method only adjusts a single crystal surface (010), and it is difficult to improve the stability of the overall structure of the precursor.

[0005] CN112151790A discloses a high-nickel ternary positive electrode material precursor and a method for controlled crystal face growth thereof, a ternary positive electrode material and a lithium ion battery. In the precursor preparation process, a metal salt solution, an alkaline solution and a complexing agent are uniformly mixed to produce a coprecipitation reaction, and the reaction kinetics are regulated to control the crystal face orientation of the crystal growth, so that the primary particles grow preferentially along the crystal face. At the same time, the diffraction peak I of the precursor XRD is 101 with I 001 The strength is controllable, thus shortening the transmission distance of lithium ions in structure, significantly improving the lithium ion diffusion coefficient, and improving the rate performance and first-cycle coulomb efficiency of the positive electrode material. However, this solution does not improve the crystallization performance of the crystal surface, making it difficult to ensure the structural stability of the positive electrode material precursor.

[0006] Therefore, it is necessary to provide a positive electrode material precursor with a stable structure and a preparation method and application thereof. Summary of the invention

[0007] The object of the present invention is to provide a structurally stable cathode material precursor and a preparation method and application thereof. The preparation method adjusts the crystal plane size of the obtained cathode material and optimizes the crystal structure of the obtained cathode material precursor through the use of a specific complexing agent solution, thereby improving the crystal structure stability of the corresponding cathode material.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a positive electrode material precursor with a stable structure, the preparation method comprising the following steps:

[0010] A metal salt solution, ammonia water, a complexing agent solution and a precipitant solution are mixed in parallel in the base liquid to carry out a co-precipitation reaction to obtain the positive electrode material precursor with a stable structure.

[0011] The complexing agent in the complexing agent solution includes ammonia water and an organic acid, and the molar ratio of ammonium radical in ammonia water to carboxyl radical (-COOH) in the organic acid is (0.1-5):1, for example, it can be 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1 or 5:1.

[0012] The preparation method provided by the present invention uses a specific complexing agent solution and adjusts the ammonium ion concentration and the carboxyl concentration to control the crystal plane size of the obtained positive electrode material precursor. Since the crystal plane size of the obtained positive electrode material is adjusted, the crystal structure of the obtained positive electrode material precursor is optimized, thereby improving the crystal structure stability of the corresponding positive electrode material; moreover, the preparation method provided by the present invention does not require the preparation of seed crystals, and can achieve a tap density TD of 1.5-2.2 g / cm 3 Specific surface area BET is 10-15m 2 / g, SPAN value is 0.2-0.7, diffraction intensity ratio I 101 / I 001 1-1.5, D 001 15-20nm, D 100 26-32nm, D 101 is 15-20nm, and D 101 / D 001 Preparation of positive electrode material precursor with a viscosity of 0.8-1.2.

[0013] Preferably, the organic acid includes any one or a combination of at least two of formic acid (CH2O2), acetic acid (CH3COOH), oxalic acid (H2C2O4), or lactic acid (C3H6O3). Typical but non-limiting combinations include a combination of formic acid and acetic acid, a combination of acetic acid and oxalic acid, a combination of acetic acid and lactic acid, a combination of formic acid, acetic acid, and oxalic acid, a combination of acetic acid, oxalic acid, and lactic acid, or a combination of formic acid, acetic acid, oxalic acid, and lactic acid.

[0014] Preferably, the pH value of the complexing agent solution is 7.5 - 10, and it can be, for example, 7.5, 8, 9, or 10, etc.

[0015] The complexing agent of the complexing agent solution in the present invention includes ammonia water and an organic acid, and the pH value is adjusted by the amount of solvent water.

[0016] Preferably, the metal salts in the metal salt solution include nickel salts, cobalt salts, and manganese salts.

[0017] Preferably, the nickel salt includes any one or a combination of at least two of nickel sulfate, nickel nitrate, nickel chloride, or nickel acetate. Typical but non-limiting combinations include a combination of nickel sulfate and nickel nitrate, a combination of nickel nitrate and nickel chloride, a combination of nickel chloride and nickel acetate, or a combination of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate.

[0018] Preferably, the cobalt salt includes any one or a combination of at least two of cobalt sulfate, cobalt nitrate, cobalt chloride, or cobalt acetate. Typical but non-limiting combinations include a combination of cobalt sulfate and cobalt nitrate, a combination of cobalt nitrate and cobalt chloride, a combination of cobalt chloride and cobalt acetate, or a combination of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate.

[0019] Preferably, the manganese salt includes any one or a combination of at least two of manganese sulfate, manganese nitrate, manganese chloride, or manganese acetate. Typical but non-limiting combinations include a combination of manganese sulfate and manganese nitrate, a combination of manganese nitrate and manganese chloride, a combination of manganese chloride and manganese acetate, or a combination of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.

[0020] Preferably, the total molar concentration of nickel, cobalt, and manganese in the metal salt solution is 0.1 - 5 mol / L, and it can be, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, or 5 mol / L, etc.

[0021] Preferably, the molar ratio of Ni, Co, and Mn in the metal salt solution is a:b:c, where 0.8 < a < 1, 0 < b < 0.2, 0 < c < 0.2, and a + b + c = 1.

[0022] Preferably, the bottom liquid is composed of deionized water, sodium hydroxide solution, and ammonia water.

[0023] Preferably, the pH value of the base solution is 7.5-12, for example, it can be 7.5, 8, 9, 10, 11 or 12.

[0024] Preferably, the ammonia concentration of the base solution is 0.1-10 g / L, for example, it can be 0.1 g / L, 1 g / L, 3 g / L, 5 g / L, 8 g / L or 10 g / L.

[0025] Preferably, the concentration of the precipitant solution used in the present invention is 7-15 g / L, for example, it can be 7 g / L, 8 g / L, 10 g / L, 12 g / L or 15 g / L.

[0026] Preferably, the coprecipitation reaction comprises a first reaction, a second reaction and a third reaction performed sequentially.

[0027] The target particle size D50 of the first reaction is 3.8-4.2 μm, for example, 3.8 μm, 4 μm or 4.2 μm.

[0028] The target particle size D50 of the second reaction is 5.8-6.2 μm, for example, 5.8 μm, 6 μm or 6.2 μm.

[0029] The target particle size D50 of the third reaction is 8-18 μm, for example, 8 μm, 10 μm, 12 μm, 15 μm or 18 μm.

[0030] Preferably, the temperature of the first reaction is 40-75°C, for example, 40°C, 50°C, 60°C, 70°C or 75°C.

[0031] Preferably, the pH value of the first reaction is 9-12, for example, 9, 10, 11 or 12.

[0032] Preferably, during the first reaction, the ammonia concentration in the system is 1-10 g / L, for example, 1 g / L, 3 g / L, 5 g / L, 8 g / L or 10 g / L.

[0033] Preferably, during the first reaction, the molar ratio of carboxyl to ammonium in the system is (0.02-0.1):1, for example, it can be 0.02:1, 0.05:1, 0.06:1, 0.08:1 or 0.1:1.

[0034] In the first reaction provided by the present invention, the pH value, ammonia concentration and the molar ratio of carboxyl groups to amino groups in the system of the first reaction are adjusted by adjusting the flow rates of the metal salt solution, ammonia water, complexing agent solution and precipitant solution. The molar ratio of carboxyl groups to ammonium groups in the system refers to the molar ratio between the carboxyl groups of the organic acid and the amino groups of the ammonia water in the system.

[0035] Preferably, the temperature of the second reaction is 40-75°C, for example, 40°C, 50°C, 60°C, 70°C or 75°C.

[0036] Preferably, during the second reaction, the flow rates of the metal salt solution, ammonia water and precipitant solution are 1.2-1.5 times of those during the first reaction, for example, 1.2 times, 1.3 times, 1.4 times or 1.5 times.

[0037] Preferably, during the second reaction, the molar ratio of carboxyl groups to ammonium groups in the system is (0.02-0.1):1, for example, it can be 0.02:1, 0.05:1, 0.06:1, 0.08:1 or 0.1:1.

[0038] In the second reaction provided by the present invention, the pH value, ammonia concentration and the molar ratio of carboxyl groups to amino groups in the system of the second reaction are adjusted by adjusting the flow rates of the metal salt solution, ammonia water, complexing agent solution and precipitant solution. The molar ratio of carboxyl groups to ammonium groups in the system refers to the molar ratio between the carboxyl groups of the organic acid and the amino groups of the ammonia water in the system.

[0039] Preferably, the temperature of the third reaction is 40-75°C, for example, 40°C, 50°C, 60°C, 70°C or 75°C.

[0040] Preferably, during the third reaction, the flow rates of the metal salt solution, ammonia water and precipitant solution are 1.2-2 times of those during the first reaction, for example, 1.2 times, 1.5 times, 1.6 times, 1.8 times or 2 times.

[0041] Preferably, during the third reaction, the molar ratio of carboxyl groups to ammonium groups in the system is (0.1-1):1, for example, it can be 0.1:1, 0.3:1, 0.5:1, 0.8:1 or 1:1.

[0042] In the third reaction provided by the present invention, the pH value, ammonia concentration and the molar ratio of carboxyl groups to amino groups in the system of the third reaction are adjusted by adjusting the flow rates of the metal salt solution, ammonia water, complexing agent solution and precipitant solution. The molar ratio of carboxyl groups to ammonium groups in the system refers to the molar ratio between the carboxyl groups of the organic acid and the amino groups of the ammonia water in the system.

[0043] Preferably, the coprecipitation reaction is carried out under stirring conditions.

[0044] Preferably, the stirring speed of the first reaction is 350-500 rpm, for example, 350 rpm, 400 rpm, 450 rpm or 500 rpm.

[0045] Preferably, the stirring speed of the second reaction is 350-500 rpm, for example, 350 rpm, 400 rpm, 450 rpm or 500 rpm.

[0046] Preferably, the stirring speed of the third reaction decreases with the increase of the particle size D50.

[0047] Preferably, during the third reaction, the stirring speed decreases by 10-30 rpm for every 1 μm increase in the particle size D50, for example, it may be 10 rpm, 15 rpm, 20 rpm, 25 rpm or 30 rpm.

[0048] In a second aspect, the present invention provides a positive electrode material precursor with a stable structure, wherein the tap density TD of the positive electrode material precursor is 1.5-2.2 g / cm 3 , the specific surface area BET is 10-15m 2 / g, SPAN value is 0.2-0.7, diffraction intensity ratio I 101 / I 001 It is 1-1.5.

[0049] The crystal plane size of the positive electrode precursor satisfies: D 001 15-20nm, D 100 26-32nm, D 101 is 15-20nm, and D 101 / D 001 It is 0.8-1.2.

[0050] The SPAN value refers to the corresponding relationship among the particle size D90, the particle size D10 and the particle size D50, that is, SPAN is (D90-D10) / D50.

[0051] Among them, D 001 Refers to the grain size of the 001 crystal plane, D 100 Refers to the grain size of the 100-plane crystal, D 101 Refers to the grain size of the 101 crystal plane.

[0052] In a third aspect, the present invention provides a positive electrode material, which is prepared from the structurally stable positive electrode material precursor described in the second aspect, or prepared from the structurally stable positive electrode material precursor obtained by the preparation method described in the first aspect.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The preparation method provided by the present invention uses a specific complexing agent solution and adjusts the ammonium ion concentration and the carboxyl concentration to control the crystal plane size of the obtained positive electrode material precursor. Since the crystal plane size of the obtained positive electrode material is adjusted, the crystal structure of the obtained positive electrode material precursor is optimized, thereby improving the crystal structure stability of the corresponding positive electrode material; moreover, the preparation method provided by the present invention does not require the preparation of seed crystals, and can achieve a tap density TD of 1.5-2.2 g / cm 3 Specific surface area BET is 10-15m 2 / g, SPAN value is 0.2-0.7, diffraction intensity ratio I 101 / I 001 1-1.5, D 001 15-20nm, D 100 26-32nm, D 101 is 15-20nm, and D 101 / D 001 Preparation of positive electrode material precursor with a viscosity of 0.8-1.2. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a scanning electron microscope image of the positive electrode material precursor obtained in Example 1. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0057] In a specific embodiment of the present invention, the chemical formula of the obtained positive electrode material precursor is Ni 0.95 Co 0.02 Mn 0.03 (OH)2, the above description is only for the purpose of clearly illustrating the technical solution and is not to be regarded as a further limitation of the present invention.

[0058] Example 1

[0059] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0060] A metal salt solution, ammonia water, a chelating agent solution and a sodium hydroxide solution with a concentration of 12 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere. Then, the mixture is washed, dried, sieved and iron is removed to obtain a positive electrode material precursor with a stable structure.

[0061] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 11, the ammonia concentration is 5 g / L, and the dissolved oxygen content in the base liquid is controlled below 1000 ppm.

[0062] The metal salt in the metal salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 2 mol / L.

[0063] The complexing agent in the complexing agent solution includes ammonia water and formic acid, and the molar ratio of ammonium radical in the ammonia water to carboxyl radical in the formic acid is 1:1; the pH value of the complexing agent solution is 8.5.

[0064] The coprecipitation reaction includes a first reaction, a second reaction and a third reaction which are performed sequentially.

[0065] The temperature of the first reaction is 65°C, the pH value is 10, the ammonia concentration is 4 g / L, and the molar ratio of carboxyl to ammonium in the system is 0.05:1; the first reaction is carried out under stirring conditions at a rotation speed of 380 rpm; the target particle size D50 of the first reaction is 4 μm.

[0066] The temperature of the second reaction is 65°C, the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.2 times that of the first reaction, and the molar ratio of carboxyl to ammonium in the system is 0.1:1; the second reaction is carried out under stirring conditions at a rotation speed of 380 rpm; the target particle size D50 of the second reaction is 6 μm.

[0067] The temperature of the third reaction is 65°C, the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.5 times that of the first reaction, and the molar ratio of carboxyl to ammonium radical in the system is 0.5:1; during the third reaction, the stirring speed decreases by 20 rpm for every 1 μm increase in particle size D50; the target particle size D50 of the third reaction is 12 μm.

[0068] The SEM image of the positive electrode material precursor with stable structure obtained in this embodiment is as follows: Figure 1 shown.

[0069] Example 2

[0070] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0071] A metal salt solution, ammonia water, a complexing agent solution and a sodium hydroxide solution with a concentration of 7 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere. Then, the mixture is washed, dried, sieved and iron is removed to obtain a positive electrode material precursor with a stable structure.

[0072] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 7.5, the ammonia concentration is 0.1 g / L, and the dissolved oxygen content in the base liquid is controlled below 1000 ppm.

[0073] The metal salt in the metal salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 0.1 mol / L.

[0074] The complexing agent in the complexing agent solution includes ammonia water and acetic acid, and the molar ratio of ammonium radical in the ammonia water to carboxyl radical in the acetic acid is 0.1:1; the pH value of the complexing agent solution is 7.5.

[0075] The coprecipitation reaction includes a first reaction, a second reaction and a third reaction which are performed sequentially.

[0076] The temperature of the first reaction is 40°C, the pH value is 9, the ammonia concentration is 1 g / L, and the molar ratio of carboxyl to ammonium in the system is 0.02:1; the first reaction is carried out under stirring conditions at a rotation speed of 300 rpm; the target particle size D50 of the first reaction is 3.8 μm.

[0077] The temperature of the second reaction is 40°C, the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.4 times that of the first reaction, and the molar ratio of carboxyl to ammonium in the system is 0.02:1; the second reaction is carried out under stirring conditions at a rotation speed of 300 rpm; the target particle size D50 of the second reaction is 5.8 μm.

[0078] The temperature of the third reaction is 40°C, the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.2 times that of the first reaction, and the molar ratio of carboxyl to ammonium radical in the system is 0.1:1; during the third reaction, the stirring speed decreases by 10 rpm for every 1 μm increase in particle size D50; the target particle size D50 of the third reaction is 8 μm.

[0079] Example 3

[0080] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0081] A metal salt solution, ammonia water, a complexing agent solution and a sodium hydroxide solution with a concentration of 15 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere. Then, the mixture is washed, dried, sieved and iron is removed to obtain a positive electrode material precursor with a stable structure.

[0082] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 12, the ammonia concentration is 10g / L, and the dissolved oxygen content in the base liquid is controlled below 1000ppm.

[0083] The metal salts in the metal salt solution include nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 5 mol / L.

[0084] The complexing agent in the complexing agent solution includes ammonia water and oxalic acid, and the molar ratio of the ammonium radical in the ammonia water to the carboxyl radical in the oxalic acid is 5:1; and the pH value of the complexing agent solution is 10.

[0085] The coprecipitation reaction includes a first reaction, a second reaction and a third reaction which are performed sequentially.

[0086] The temperature of the first reaction is 75°C, the pH value is 12, the ammonia concentration is 10g / L, and the molar ratio of carboxyl to ammonium in the system is 0.1:1; the first reaction is carried out under stirring conditions at a rotation speed of 500rpm; the target particle size D50 of the first reaction is 4.2μm.

[0087] The temperature of the second reaction is 75° C., the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.5 times that of the first reaction, and the molar ratio of carboxyl to ammonium radical in the system is 0.1:1; the second reaction is carried out under stirring conditions with a rotation speed of 500 rpm; the target particle size D50 of the second reaction is 6.2 μm;

[0088] The temperature of the third reaction is 40°C, the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are each independently twice that of the first reaction, and the molar ratio of carboxyl groups to ammonium groups in the system is 1:1; during the third reaction, the stirring speed decreases by 30 rpm for every 1 μm increase in particle size D50; the target particle size D50 of the third reaction is 18 μm.

[0089] Example 4

[0090] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0091] A metal salt solution, ammonia water, a complexing agent solution and a sodium hydroxide solution with a concentration of 12 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere, and then washed, dried, sieved and iron removed to obtain a positive electrode material precursor with a stable structure;

[0092] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 11, the ammonia concentration is 5g / L, and the dissolved oxygen content in the base liquid is controlled below 1000ppm;

[0093] The metal salt in the metal salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 2 mol / L;

[0094] The complexing agent in the complexing agent solution includes ammonia water and formic acid, and the molar ratio of the ammonium group in the ammonia water to the carboxyl group in the formic acid is 1:1; the pH value of the complexing agent solution is 8.5;

[0095] The coprecipitation reaction comprises a first reaction, a second reaction and a third reaction performed sequentially;

[0096] The temperature of the first reaction is 65°C, the pH value is 10, the ammonia concentration is 4 g / L, and the molar ratio of carboxyl to ammonium in the system is 0.05:1; the first reaction is carried out under stirring conditions with a rotation speed of 380 rpm; the target particle size D50 of the first reaction is 4 μm;

[0097] The temperature of the second reaction is 65° C., the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.2 times that of the first reaction, and the molar ratio of carboxyl to ammonium radical in the system is 0.1:1; the second reaction is carried out under stirring conditions at a rotation speed of 380 rpm; the target particle size D50 of the second reaction is 6 μm;

[0098] The temperature of the third reaction is 65°C, the flow rates of the metal salt solution, ammonia water and sodium hydroxide solution are independently 1.5 times that of the first reaction, and the molar ratio of carboxyl to ammonium radical in the system is 0.5:1; the third reaction is carried out under stirring conditions at a rotation speed of 380 rpm; the target particle size D50 of the third reaction is 12 μm.

[0099] Example 5

[0100] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0101] A metal salt solution, ammonia water, a complexing agent solution and a sodium hydroxide solution with a concentration of 12 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere, and then washed, dried, sieved and iron removed to obtain a positive electrode material precursor with a stable structure;

[0102] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 11, the ammonia concentration is 5g / L, and the dissolved oxygen content in the base liquid is controlled below 1000ppm;

[0103] The metal salt in the metal salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 2 mol / L;

[0104] The complexing agent in the complexing agent solution includes ammonia water and formic acid, and the molar ratio of the ammonium group in the ammonia water to the carboxyl group in the formic acid is 1:1; the pH value of the complexing agent solution is 8.5;

[0105] The coprecipitation reaction comprises a first reaction;

[0106] The temperature of the first reaction is 65°C, the pH value is 10, the ammonia concentration is 4g / L, and the molar ratio of carboxyl to ammonium in the system is 0.05:1; the first reaction is carried out under stirring conditions at a rotation speed of 380rpm; the target particle size D50 of the first reaction is 12μm.

[0107] Example 6

[0108] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0109] A metal salt solution, ammonia water, a complexing agent solution and a sodium hydroxide solution with a concentration of 12 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere, and then washed, dried, sieved and iron removed to obtain a positive electrode material precursor with a stable structure;

[0110] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 11, the ammonia concentration is 5g / L, and the dissolved oxygen content in the base liquid is controlled below 1000ppm;

[0111] The metal salt in the metal salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 2 mol / L;

[0112] The complexing agent in the complexing agent solution includes ammonia water and formic acid, and the molar ratio of the ammonium group in the ammonia water to the carboxyl group in the formic acid is 1:1; the pH value of the complexing agent solution is 8.5;

[0113] The coprecipitation reaction is the second reaction;

[0114] The conditions of the second reaction were the same as those of the second reaction in Example 1, and the target particle size D50 of the second reaction was 12 μm.

[0115] Example 7

[0116] This embodiment provides a method for preparing a positive electrode material precursor with a stable structure, and the preparation method comprises the following steps:

[0117] A metal salt solution, ammonia water, a complexing agent solution and a sodium hydroxide solution with a concentration of 12 g / L are mixed in parallel in the base liquid, and a co-precipitation reaction is carried out in a nitrogen atmosphere, and then washed, dried, sieved and iron removed to obtain a positive electrode material precursor with a stable structure;

[0118] The base liquid is composed of deionized water, sodium hydroxide solution and ammonia water. The pH value of the base liquid is 11, the ammonia concentration is 5g / L, and the dissolved oxygen content in the base liquid is controlled below 1000ppm;

[0119] The metal salt in the metal salt solution includes nickel sulfate, cobalt sulfate and manganese sulfate, and the total molar concentration of nickel, cobalt and manganese is 2 mol / L;

[0120] The complexing agent in the complexing agent solution includes ammonia water and formic acid, and the molar ratio of the ammonium group in the ammonia water to the carboxyl group in the formic acid is 1:1; the pH value of the complexing agent solution is 8.5;

[0121] The coprecipitation reaction is the third reaction;

[0122] The conditions of the third reaction are the same as those of the third reaction in Example 1, and the target particle size D50 of the third reaction is 12 μm.

[0123] Comparative Example 1

[0124] This comparative example provides a method for preparing a positive electrode material precursor, which is the same as Example 1 except that the molar amount of formic acid in the complexing agent solution is replaced by ammonia water, and the molar ratio of carboxyl groups to ammonium groups in the system is not controlled during the first reaction, the second reaction, and the third reaction.

[0125] Performance measurement

[0126] The particle size D50, SPAN value, tap density TD, specific surface area BET, diffraction intensity I of the positive electrode material precursors obtained in the above examples and comparative examples are as follows: 101 / I 001 , D 001 , D 100 and D 101 The results are shown in Table 1.

[0127] Table 1

[0128]

[0129] The positive electrode material precursors obtained in the above examples and comparative examples are used to prepare positive electrode materials:

[0130] Li2CO3 and the cathode material precursor are uniformly mixed by a high-speed mixer and sintered in an air atmosphere at a temperature of 800°C for 12 hours to obtain the cathode material; the theoretical molar ratio of lithium in Li2CO3 to the precursor is 1.03:1, and the ignition loss is supplemented according to the loss caused by sintering.

[0131] The positive electrode material, the binder polyvinylidene fluoride and the conductive agent Super P are added to N-methylpyrrolidone at a mass ratio of 97:1.5:1.5 and stirred to form a first positive electrode slurry; the first positive electrode slurry is then evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying and rolling;

[0132] Graphite, conductive agent acetylene black, thickener CMC and binder SBR are mixed in a mass ratio of 96:1:1.5:1.5, and deionized water is added as a solvent and stirred to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing and slitting;

[0133] Ethylene carbonate EC, ethyl methyl carbonate EMC, and diethyl carbonate DEC are mixed in a volume ratio of 1:1:1, and then fully dried lithium salt LiPF6 is dissolved in the mixed solvent to prepare an electrolyte with a concentration of 1 mol / L;

[0134] The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, then wrapped with an aluminum-plastic film, and injected with an electrolyte after drying. After packaging, standing and forming, a lithium-ion battery is obtained; the separator is a PE porous film with a thickness of 11 μm, an air permeability of 280 s / 100 mL, and a porosity of 40%.

[0135] The first discharge specific capacity and cycle capacity retention rate of the obtained lithium ion battery were tested, wherein, at 25°C, the lithium ion battery was charged and discharged at a rate of 0.04A / g (calculated based on the mass of the positive electrode material) in a voltage range of 2V to 4.3V, and the first discharge specific capacity was measured; at 25°C, the battery was cycled at a rate of 0.19A / g (calculated based on the mass of the positive electrode material), and after 500 cycles, the discharge capacity of the battery at this time was divided by the discharge capacity of the first cycle, i.e., the 500-cycle capacity retention rate of the battery; the results are shown in Table 2.

[0136] Table 2

[0137] First discharge specific capacity (mAh / g) Cycle capacity retention rate (%) Example 1 245.98 93.2% Example 2 238.27 91.1% Example 3 236.45 89.6% Example 4 220.11 85.5% Example 5 219.80 86.3% Example 6 200.20 83.4% Example 7 198.5 83.0% Comparative Example 1 187.6 80.0%

[0138] In summary, the preparation method provided by the present invention controls the crystal plane size of the obtained positive electrode material precursor by adjusting the concentration of ammonium ions and the concentration of carboxyl groups through the use of a specific complexing agent solution. Since the crystal plane size of the obtained positive electrode material is adjusted, the crystal structure of the obtained positive electrode material precursor is optimized, thereby improving the crystal structure stability of the corresponding positive electrode material; moreover, the preparation method provided by the present invention does not require the preparation of seed crystals, and can achieve a tap density TD of 1.5-2.2 g / cm 3 Specific surface area BET is 10-15m 2 / g, SPAN value is 0.2-0.7, diffraction intensity ratio I 101 / I 001 1-1.5, D 001 15-20nm, D 100 26-32nm, D 101 is 15-20nm, and D 101 / D 001 Preparation of positive electrode material precursor with a viscosity of 0.8-1.2.

[0139] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a structurally stable cathode material precursor, characterized in that: The preparation method includes the following steps: A metal salt solution, ammonia water, a complexing agent solution, and a precipitating agent solution are mixed in parallel in a bottom solution to carry out a coprecipitation reaction to obtain the precursor of the structurally stable cathode material; The complexing agent in the complexing agent solution includes ammonia water and an organic acid, and the molar ratio of ammonium in the ammonia water to carboxyl in the organic acid is (0.1-5):

1.

2. The preparation method according to claim 1, characterized in that: The organic acid includes any one or a combination of at least two of formic acid, acetic acid, oxalic acid, or lactic acid; Preferably, the pH value of the complexing agent solution is 7.5-10.

3. The preparation method according to claim 1 or 2, characterized in that: The metal salt in the metal salt solution includes a nickel salt, a cobalt salt, and a manganese salt; Preferably, the molar ratio of Ni, Co, and Mn in the metal salt solution is a:b:c, where 0.8 < a < 1, 0 < b < 0.2, 0 < c < 0.2, and a + b + c = 1.

4. The preparation method according to any one of claims 1 to 3, characterized in that The coprecipitation reaction includes a first reaction, a second reaction, and a third reaction carried out in sequence; The target particle size D50 of the first reaction is 3.8-4.2 μm; The target particle size D50 of the second reaction is 5.8-6.2 μm; The target particle size D50 of the third reaction is 8-18 μm.

5. The preparation method according to claim 4, characterized in that: The temperature of the first reaction is 40-75°C; Preferably, the pH value of the first reaction is 9-12; Preferably, during the first reaction, the ammonia concentration in the system is 1-10 g / L; Preferably, during the first reaction, the molar ratio of carboxyl to ammonium in the system is (0.02-0.1):

1.

6. The preparation method according to claim 4 or 5, characterized in that: The temperature of the second reaction is 40-75°C; Preferably, during the second reaction, the flow rates of the metal salt solution, ammonia water, and precipitating agent solution are 1.2-1.5 times those of the first reaction; Preferably, during the second reaction, the molar ratio of carboxyl to ammonium in the system is (0.02-0.1):

1.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The temperature of the third reaction is 40-75°C; Preferably, during the third reaction, the flow rates of the metal salt solution, ammonia water, and precipitating agent solution are 1.2-2 times those of the first reaction; Preferably, during the third reaction, the molar ratio of carboxyl to ammonium in the system is (0.1-1):

1.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The coprecipitation reaction is carried out under stirring conditions; Preferably, the stirring speed of the first reaction is 350-500 rpm; Preferably, the stirring speed of the second reaction is 350-500 rpm; Preferably, the stirring speed of the third reaction decreases as the particle size D50 increases.

9. A structurally stable cathode material precursor, characterized in that: The tap density TD of the positive electrode material precursor is 1.5-2.2 g / cm 3 , the specific surface area BET is 10-15m 2 / g, SPAN value is 0.2-0.7, diffraction intensity ratio I 101 / I 001 1-1.5; The crystal plane size of the positive electrode precursor satisfies: D 001 15-20nm, D 100 26-32nm, D 101 is 15-20nm, and D 101 / D 001 It is 0.8-1.

2.

10. A positive electrode material, characterized in that: The cathode material is prepared from the precursor of the structurally stable cathode material described in claim 9, or from the precursor of the structurally stable cathode material obtained by the preparation method described in any one of claims 1-8.

Citation Information

Patent Citations

  • High-nickel ternary positive electrode material precursor and crystal face controllable growth method thereof, ternary positive electrode material and lithium ion battery

    CN112151790A

  • Production device for preparing ammonium formate through continuous ammoniation of formic acid

    CN114762812A

  • Dryer for ammonium formate production

    CN218047249U

Cited By

  • Nickel-cobalt-manganese ternary positive electrode material and preparation method and application thereof

    CN120089733A

  • A nickel-cobalt-manganese ternary cathode material, its preparation method and application

    CN120089733B